2013
DOI: 10.1890/12-0359.1
|View full text |Cite
|
Sign up to set email alerts
|

Gradient‐based habitat affinities predict species vulnerability to drought

Abstract: Ecological fingerprints of climate change are becoming increasingly evident at broad geographical scales as measured by species range shifts and changes in phenology. However, finer-scale species-level responses to environmental fluctuations may also provide an important bellwether of impending future community responses. Here we examined changes in abundance of butterfly species along a hydrological gradient of six montane meadow habitat types in response to drought. Our data collection began prior to the dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…The shifts in community composition during the drought year were most extensive at wetter, cooler sites (with high actual‐to‐potential evapotranspiration ratio, APET). Whilst counter to our prediction, this result is consistent with previous research: Debinski et al (, ) found that the most prominent changes in butterfly communities during a drought were in wet rather than dry meadows, potentially driven by shifts in vegetation towards drought‐tolerant plants. Indeed, plant community change in response to climatic perturbations can be more extreme in wetter rather than drier sites (Kardol et al ), while the condition of plants and their suitability as butterfly host‐plants may also be affected (Gibbs et al ).…”
Section: Discussionsupporting
confidence: 86%
“…The shifts in community composition during the drought year were most extensive at wetter, cooler sites (with high actual‐to‐potential evapotranspiration ratio, APET). Whilst counter to our prediction, this result is consistent with previous research: Debinski et al (, ) found that the most prominent changes in butterfly communities during a drought were in wet rather than dry meadows, potentially driven by shifts in vegetation towards drought‐tolerant plants. Indeed, plant community change in response to climatic perturbations can be more extreme in wetter rather than drier sites (Kardol et al ), while the condition of plants and their suitability as butterfly host‐plants may also be affected (Gibbs et al ).…”
Section: Discussionsupporting
confidence: 86%
“…clodius was more broadly distributed across the Teton region than expected based on previous studies in the area (Debinski et al 2006(Debinski et al , 2013, occupying 78% of the meadows we predicted would be suitable in 2013. These results are encouraging in the context of long-term population viability.…”
Section: Discussioncontrasting
confidence: 44%
“…From 1997to 2007, Debinski et al (2006, 2010 collected vegetation and butterfly distribution data across this hydrological gradient within 55 montane meadows in the GYE, including 25 meadows in the Teton region. Butterfly abundance counts from these surveys indicated that Parnassius butterflies were most often found in mesic and xeric meadows (Debinski et al 2013). Furthermore, Auckland et al (2004) Of the 61 sites, 41 sites were surveyed as part of the study in 2013, three sites were not classified as potential habitat when ground-truthed and were removed from the study, nine sites were excluded due to inaccessibility (> 4.5 km from an access road), and the flight season ended before we were able to survey the remaining eight sites.…”
Section: Study Areamentioning
confidence: 97%
See 1 more Smart Citation
“…This pattern could potentially represent a gradient of water availability from xeric to mesic to hydric. Intermediate values also may be an indicator of mesic meadow types, which have been shown in other regions to exhibit higher sensitivities to climate variability relative to more xeric or hydric meadows (Debinski, Jakubauskas, & Kindscher, ; Debinski, Caruthers, Cook, Crowley, & Wickham, ; Debinski, Wickham, Kindscher, Caruthers, & Germino, ).…”
Section: Discussionmentioning
confidence: 99%